PENGARUH DESAIN DINDING SUSUNAN BATA BERONGGA SEBAGAI SELUBUNG BANGUNAN TERHADAP KENYAMANAN TERMAL RUANG KELAS SEKOLAH ALFA OMEGA TANGERANG - Alfred Aritonang, Dickinson; Yusnita Nugroho, Nancy (Jurnal Riset Arsitektur, 2022)
Abstrak - Alfa Omega School is a school that has a design that responds to nature. The design strategy is made in such a way that in terms of design concepts, it answers the climate problems in which the school is built. Located in an area that has a tropical climate, with more specifically swamps and rice fields, the climate around the place feels uncomfortable with high temperatures and humidity levels that are above the level of thermal comfort for activities. The school is designed by processing the building skin. Raw Architect, as the party who designed this school, chose brick material for the main reason of raising the locality in the area. In addition, by using brick material as part of the architectural elements in the building, they can create a carbon footprint to a minimum, namely emissions from human activities that in a long time will have a negative impact on nature, which means they can create designs that are not only elevating locality but also environmentally friendly. The purpose of this research is to see whether the effect of deinding with hollow brick arrangement in the room building envelope design on the thermal comfort that is being made in the Alfa Omega School design. This research is an evaluative-experimental research with a quantitative approach by describing conditions and conditions both in terms of architectural and thermal comfort, which are then compared to the theory of thermal comfort in general and more specifically as a school. This research was conducted indirectly through the media of computers, the internet, and a simulation program to measure the level of thermal comfort at the Alpha Omega School. The result of his research is an understanding of how the influence of the wall with a hollow brick arrangement as a building envelope in response to the existing climate in the area, so that it can be understood how the ability of the tire walls in the space to achieve thermal comfort that can support the activity in it as school. And if thermal discomfort is found in the application of this material as a building envelope, a way to optimize its thermal quality will be sought with simulation theories and experiments. Keywords: Thermal comfort, building envelope, holey walls, schools